Research on intelligent scheme of telecommunication network - Tao LI; Chunjia WANG; Shanshan LI (Dianxin kexue)
The network of telecom operators needs to be promoted urgently in agility, efficiency and intelligence to realize its self-configuration, self-management and self-optimization.However, due to the inconsistent development route and technical characteristics between AI and communication network, how to deeply integrate AI and communication network is necessary to be considered systematically.Based on the development of the telecommunication network intelligence industry, and on the basis of the analysis of the needs of telecom operators for intelligence and the assessment of the status quo, the goal and technical scheme of telecommunication network intelligence were proposed, which covered the intelligent framework, intelligent functional modules and processes, data processing, algorithm model construction and integration.The scheme was helpful to promote the large-scale intellectualization of telecom operators and improve operational efficiency.